Study on General Morphology and Length-Weight Relationship of Indigenous Ornamental Fish Badis Badis (Hamilton, 1822) from West Bengal - Mohua Dutta; S. Bhattacharya; B. Mondal; B. K. Mahapatra (Journal of Indian Fisheries Association, 2018)
Among the small indigenous ornamental perch grouped species, Badis badis (Hamilton, 1822) of family Badidae, is one of the most highly demanding fish for both local and export market due to their chameleonic habit. Hence morphological characters and length weight relationship of the species was studied. A total 20 morphometric and 8 meristic characters revealed that the standard length is about 79.59% and head length about 24.41% of total length of the fish. The eye diameter is about 33.33% of head length of the fish. Length-weight relationship and condition factor were estimated based on 464 specimens collected from Dattafuliya, North 24 Parganas during March, 2017 to February, 2018. The total length ranged from 16.5-59.3 mm and the total body weight ranged from 0.05-2.52 g. The length weight relationship is established as Log W= -5.043+3.133L and the r2 value is 0.957. The condition factor of the fish was also observed as 1.61 indicating a good condition of the species in the present habitat.